All Rights Reserved - Katsoulis, Gregory Scott (Don Mills, Ontario, Canada Harlequin Teen, 2017)
"Speth Jime is anxious to deliver her Last Day speech and celebrate her transition into adulthood. The moment she turns fifteen, Speth must pay for every word she speaks ('Sorry' is a flat ten dollars and a legal admission of guilt), for every nod ($0.99/sec), for every scream ($0.99/ sec) and even every gesture of affection. She's been raised to know the consequences of falling into debt, and can't begin to imagine the pain of having her eyes shocked for speaking words that she's unable to afford"--Dust jacket flap.
Keywords: Freedom of expression -- Juvenile fiction; Mutism, Elective -- Juvenile fiction; Silence -- Juvenile fiction; Copyright -- Juvenile fiction; Patents -- Juvenile fiction; Trademarks -- Juvenile fiction; Freedom of expression -- Fiction; Mutism, Elective -- Fiction; Silence -- Fiction; Copyright -- Fiction; Patents -- Fiction; Trademarks -- Fiction